INFLUENCE OF COLLOID-CHEMICAL STATE OF HEAVY METALS IONS ON MOФHOLOGY AND PHASE COMPOSITION OF THEIR OXIDE FORMS (Fe) - A. S. Panasugin; D. P. Mihalap; V. L. Tribushevski; S. L. Rimoshevski; V. S. Zinchenko (Литьë и металлургия)
The influence of colloid-chemical state of ions of heavy metals on morphology and phase composition of their oxide forms (compounds Fe) is considered.